Prevalence and risk factors for initiating tobacco and alcohol consumption in adolescents living in urban and rural Ethiopia. (September 2019) - Getachew, S.; Lewis, S.; Britton, J.; Deressa, W.; Fogarty, A.W.
Abstract: Objectives: African countries are potential high growth markets for the alcohol and tobacco industries. This study aimed to identify exposures that are associated with initiating use of alcohol and tobacco products in young people living in Ethiopia. As televised football and Internet viewing are media through which products can be promoted to this population efficiently, these risk factors were of particular interest. Study design: This is a cross-sectional study. Methods: Data were collected using a self-administered questionnaire of 3967 children aged 13–19 years in 20 high schools in urban and rural Ethiopia on consumption and risk factors for alcohol and tobacco use in 2016, as well as exposure to potential sources of advertising. Results: Eight percent of respondents reported having ever smoked and 3% were current smokers. Twenty-nine percent reported ever having used alcohol, and 14% were current users. Risk factors for ever smoking included father smoking (odds ratio [OR] 1.95; 95% confidence interval [CI]: 1.21 to 3.15), mother smoking (OR 3.90; 95% CI: 1.63 to 9.33), best friend smoking (OR 5.86; 95% CI: 4.31 to 7.96) and home Internet access (OR 1.75; 95% CI: 1.35 to 2.27). There was a very strong positive association between ever having smoked cigarettes and ever having tried alcohol ( P < 0.001). Risk factors for currently drinking alcohol included father drinking (OR 1.45; 95% CI: 1.05 to 2.01), mother drinking (OR 2.00; 95% CI: 1.44 to 2.77), home Internet access (OR 1.53; 95% CI: 1.24 to 1.90) and regular watching of televised football (OR 2.44 compared to those who do not; 95% CI: 1.58 to 3.78). Conclusions: As in rich countries, tobacco and alcohol use among Ethiopian teenagers increases among those exposed to family and peer use but are also more common among those accessing the Internet and, for alcohol, those watching televised football. The effect of watching televised football on alcohol use, at least, is likely to be due to exposure to advertising. Highlights: Rapid economic development is changing the environment in developing countries rapidly, generating a new potential market for the alcohol and tobacco industries. Fourteen percent of adolescents living in Ethiopia are regular consumers of alcohol, and 3% regularly smoke cigarettes. Regular watching of international football on television is associated with being a current consumer of alcohol. Public health strategies to modify alcohol and tobacco usage in adolescents living in Ethiopia need to consider that the Internet and televised football matches are potential sources of exposure to advertising aiming to promote consumption.